Complete genome sequence of the motile actinomycete Actinoplanes missouriensis 431T (= NBRC 102363T). Issue 2 (September 2012) - Yamamura, Hideki; Ohnishi, Yasuo; Ishikawa, Jun; Ichikawa, Natsuko; Ikeda, Haruo; Sekine, Mitsuo; Harada, Takeshi; Horinouchi, Sueharu; Otoguro, Misa; Tamura, Tomohiko; Suzuki, Ken-ichiro; Hoshino, Yasutaka; et al.
Abstract Actinoplanes missouriensis Couch 1963 is a well-characterized member of the genusActinoplanes, which is of morphological interest because its members typically produce sporangia containing motile spores. The sporangiospores are motile by means of flagella and exhibit chemotactic properties. It is of further interest that members ofActinoplanes are prolific sources of novel antibiotics, enzymes, and other bioactive compounds. Here, we describe the features ofA. missouriensis 431T, together with the complete genome sequence and annotation. The 8, 773, 466 bp genome contains 8, 125 protein-coding and 79 RNA genes.